Persepsi Masyarakat Kelurahan Bukit Duri Terhadap Program Normalisasi Kali Ciliwung di Jakarta Tahun 2017 Serta Variabel-Variabel yang Memengaruhinya - Loveria Candra Puspita; Achmad Prasetyo (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2017)
River normalization program is one of the ways to handle flood problems. However, not all communities accept this program. For that, we want to know the public perception towards normalization of Ciliwung River and analyze the variables that influence it. Perception data was obtained through survey with household approach in Bukit Duri Village which then analyzed by logistic regression. The results show that 28 percent of households around the river and 22 percent of households not around the river reject normalization. Household perceptions around the river are significantly influenced by sex, organizational participation, socialization, and per capita expenditure. The non-rivers are influenced by employment status, organizational participation, and socialization.